PERBAIKAN PROSES KERJA PADA PROSES PEMBONGKARAN DI PT. TOYOTA MOTOR MANUFACTURING INDONESIA - , MUHAMMAD SHALAHUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Supply chain is one of important department in manufacturing companyâs organization, which ensure matrial flow for production glibness. Just In Time is manufacturing system that make product a number of needed and when it needed, this manufacturing system is really count on a good supply chain department. Toyota is founding father of Just In Time manufacturing system and one of manufacturing company in the world which use this system. As a manufacturing company that use this system Toyota pay close attention to their supply chain department. Improvement or Kaizen is always did on this department to get better operation in order to keep matrial flow always occur fluently. In Toyota Motor Manufacturing Indonesia, supply chain department is also known as Logistic Operation Department, it having responsibility of all matrial flow operation. Unpacking area as a biginning process of matrial flow in Toyota Motor Manufacturing Indonesia is very important, production will get trouble if that area have a trouble too. In 2013 supply chain department of Toyota Motor Manufacturing Indonesia give more concern to this area, big improvement activities is carried out to achieve best operation. The improvement did by special method accordance with Toyota standardization. Unpacking area use manual method yet, by using manpower capability as prime energy to do work process. Improvement activities is focused on unpacking method in order to increase manpower eficiency. Unpacking method have to do by cyclic operation according to Toyota standardization. By cyclic operation, work process that manpower do will happen clearly, what should they do, how, why, and when they should do kind of work process will carried out clearly.